THE INFLUENCE OF THE ILL-STRUCTURED PROBLEM BASED LEARNING MODEL ON STUDENTS' SCIENCE LITERACY ABILITY IN ENVIRONMENTAL CHANGE CONCEPT - Dewi Nurhilyah; Zulfiani Zulfiani; Laila Mahmudah; Yuke Mardiati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
Problem-based learning (PBL) is an effective pedagogy in increasing scientific literacy among students, and this strategy helps students acquire and apply knowledge and develop higher-order thinking skills that prioritize problems obtained from real life.This study aims to investigate the influence of ill-structured type problem-based learning (PBL) model on students' science literacy skills in environmental change concept. The research was conducted at MAN 1 Pandeglang in the 2023/2024 school year using a quasi-experimental method using a non-equivalent control group design. Two classes were selected as research samples (experimental class and control class) through simple random sampling technique. Data analysis using independent samples t-test with the help of IBM SPSS Statistics 26 showed that the value of sig. (2-tailed) of 0.004, which is below the significance level of α = 0.05. These results show that the use of ill-structured type problem-based learning models has a significant influence on improving students' science literacy skills. Thus, this learning model is effective in improving science literacy skills on the concept of environmental change